DOSIS OPTIMUM BIJI KELOR (Moringa seed) DALAM MENURUNKAN KEKERUHAN (Turbidity) AIR SUNGAI BETAPUS DI KELURAHAN SEMPAJA UTARA KOTA SAMARINDA - Marjan Wahyuni (Jurnal Ilmiah Manuntung, 2015)
Water is used as daily necessities which must meet the standards of raw water for drinking water, household, and other – other. As in the waters of the North Sempaja Betapus Sub District of North Samarinda territory that location is dihulu Karangmumus River. Physically the water is cloudy, colored and contains organic / inorganic. The aim of this study was to determine the optimum dose of moringa seed in reducing turbidity (Turbidity) Water Betapus River in the Village of North Sempaja Samarinda.This research is a quasi-experimental (Quasi Experiment) or the design of a series of time (Time Series Design) which make measurements before and after affixing moringa seeds with sampling methods Grab Sample for 1 day. This experiment uses a method to purify raw water Jartest Betapus River by adding powdered moringa seeds (Moringan oleifera) into 1 liter of water by varying the dose of 0.5 g / L, 1.0 g / L, 1.5 g / L, and 2.0 g / L. Results of research conducted on Betapus River water showed that the level of turbidity (Turbidity) amounted to 79.1 NTU with a pH of 6.8, so it is said to be ineligible clean water turbidity according Permenkes RI 416 / Menkes / Per / IX / 1990, namely that allowed 25 NTU. After affixing moringa seeds with a variety of different doses, the results showed as follows: the dose of 0.5 g / L = 4.52 NTU; a dose of 1.0 g / L = 7.76 NTU; dose of 1.5 g / L = 9.14 NTU, and a dose of 2.0 g / L = 8.51 NTU. The optimum dose range moringa seeds needed at River raw water Betapus = 0.5 g / L with a percentage of 94.28%. For people who use the river water as the need for clean water for toilets (Bath Wash Case) and so on, you should do a simple treatment with Moringa seed powder according affixing the optimum dose prescribed to reduce levels of turbidity (Turbidity) in water.